2021
DOI: 10.1101/2021.05.31.445808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scaling principles of white matter brain connectivity

Abstract: Brains come in many shapes and sizes. Nature has endowed big-brained primate species like humans with a proportionally large cerebral cortex. White matter connectivity - the brain's infrastructure for long-range communication - might not always scale at the same pace as the cortex. We investigated the consequences of this allometric scaling for white matter brain network connectivity. Structural T1 and diffusion MRI data were collated across fourteen primate species, describing a comprehensive 350-fold range i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 64 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…The same study further demonstrated a more pronounced modular topology of the human connectome as compared to the chimpanzee connectome. Based on these findings the researchers suggested an evolutionary shift in the human brain toward investment of neural resources in multimodal connectivity facilitating neural integration, combined with an increase in language-related connectivity supporting functional specialization (Ardesch et al, 2019).…”
Section: Principles Of Crossmodal Connectivity Developmentmentioning
confidence: 98%
See 4 more Smart Citations
“…The same study further demonstrated a more pronounced modular topology of the human connectome as compared to the chimpanzee connectome. Based on these findings the researchers suggested an evolutionary shift in the human brain toward investment of neural resources in multimodal connectivity facilitating neural integration, combined with an increase in language-related connectivity supporting functional specialization (Ardesch et al, 2019).…”
Section: Principles Of Crossmodal Connectivity Developmentmentioning
confidence: 98%
“…Further support for the above view comes from a very recent study by Ardesch et al (2019) who investigated adaptations of human brain connectivity by means of comparative connectomicsthe study of differences in the topological organization of connectomes (van den Heuvel et al, 2016). This study compared and contrasted humans and chimpanzees on shared connectivity in the primary, unimodal association, and multimodal association areas (Ardesch et al, 2019).…”
Section: Principles Of Crossmodal Connectivity Developmentmentioning
confidence: 98%
See 3 more Smart Citations